Ethanol-mediated activation of the NLRP3 inflammasome in iPS cells and iPS cells-derived neural progenitor cells. Issue 1 (December 2016) - De Filippis, Lidia; Halikere, Apoorva; McGowan, Heather; Moore, Jennifer; Tischfield, Jay; Hart, Ronald; Pang, Zhiping
Abstract Background Alcohol abuse produces an enormous impact on health, society, and the economy. Currently, there are very limited therapies available, largely due to the poor understanding of mechanisms underlying alcohol use disorders (AUDs) in humans. Oxidative damage of mitochondria and cellular proteins aggravates the progression of neuroinflammation and neurological disorders initiated by alcohol abuse. Results Here we show that ethanol exposure causes neuroinflammation in both human induced pluripotent stem (iPS) cells and human neural progenitor cells (NPCs). Ethanol exposure for 24 hours or 7 days does not affect the proliferation of iPS cells and NPCs, but primes an innate immune-like response by activating the NLR family pyrin domain containing 3 (NLRP3) inflammasome pathway. This leads to an increase of microtubule-associated protein 1A/1B-light chain 3+ (LC3B+ ) autophagic puncta and impairment of the mitochondrial and lysosomal distribution. In addition, a decrease of mature neurons derived from differentiating NPCs is evident in ethanol pre-exposed compared to control NPCs. Moreover, a second insult of a pro-inflammatory factor in addition to ethanol preexposure enhances innate cellular inflammation in human iPS cells. Conclusions This study provides strong evidence that neuronal inflammation contributes to the pathophysiology of AUDs through the activation of the inflammasome pathway in human cellular models.